The δ2H and δ18O isotopic evidence for hydraulic redistribution by Alnus acuminata in an agricultural landscape - Celestin Ukozehasi; Amr Elkelish; Endrit Kullaj (Discover Agriculture, 2024)
Abstract Understanding of the process of hydraulic redistribution in agricultural landscapes is important for informing agroforestry design and agricultural management. The measurement of hydraulic lift and redistribution in the field is still a challenge. Due to the robustness of stable isotope analysis, we hypothesized that the measurement and analysis of the natural abundance of stable isotopes δ 2 H and δ1⁸O, in the twigs of agroforestry trees, stems of wheat intercrop, rain, and soil water coupled to an isotopic mixing modeling by IsoSource supplemented with other physiological crop parameters, would estimate the extent of hydraulic redistribution in intercropping, and inform the design of an agroforestry system. There are still many plant species that have not been investigated for their potential hydraulic redistribution yet, and Alnus acuminata is among them, therefore this study aimed to contribute to filling that gap. The field experiment was conducted in an Andic soil of the northern Rwanda highlands to address the extent of water efflux redistribution from tree roots of Alnus acuminata to the wheat intercrop across bench terraces. The study involved the measurement of the natural abundance of stable isotopes δ 2 H, and δ 1 ⁸O of the tree twigs, soil and wheat stems at distances of 1, 3, 5, and 7 m from the tree lines of Alnus acuminata, and of rainwater. The isotopic mixing modeling was supplemented by measuring both specific leaf area (SLA) and carbon discrimination (Δ13C) in the wheat leaf. We noted a significant (p < 0.01) gradient in the depletion of wheat xylem water δ 2 H and δ 18 O signatures moving further away from the tree lines. Based on the wheat value of δ 2 H, the isoSource indicated that the trees may have contributed the wheat water up to 64.3 ± 2.6% at 5 m from the trees, and the values of both the SLA (cm2 g–1) and ∆13C (‰) of wheat leaf indicated the water use efficiency of wheat significantly improved around the trees up to 3 m away from the trees with 140.10 ± 3.74 cm2 g–1, 149.56 ± 3.43 cm2 g–1 and 20.6 ± 0.1‰, 20.8 ± 0.1‰ at 1 m and 3 m for SLA and ∆13C respectively. We concluded that Alnus acuminata exhibits significant hydraulic redistribution in the field.